Facile Synthesis of 3D Graphene Hydrogel/Carbon Nanofibers Composites for Supercapacitor Electrode. (1st January 2015) - Wu, Yuanzhan; Liu, Suqin; Zhao, Kuangmin; Yuan, Hao; Lv, Kezhou; Ye, Guanying
Abstract : 3D graphene hydrogel/carbon nanofibers (GC) composites are synthesized via chemical reduction of graphite oxide (GO)/carbon nanofibers (CNFs) mixture at the low temperature. Because of the self-assembly process of GO to graphene hydrogel, GC has a 3D freestanding structure with the CNFs uniformly embedded into graphene nanosheets. The composites can be used as an electrode directly without using any conductive additives or binders. Encouragingly, GC exhibits excellent electrochemical performances with a high capacitance of 150 F g −1 at 1 A g −1 in 1 M Na2 SO4 electrolyte, which is superior than that of most carbon materials. Additionally, the composites present an outstanding cycling stability with 97.8% capacitance retention after 2000 cycles.